Cyber Dating Abuse Among Spanish Emerging Adults: The Moderating Role of Resilience in the Association Between Perpetration and Victimization - Beatriz Víllora; Elisa Larrañaga; Santiago Yubero; Raúl Navarro (SAGE Open)
Cyber dating abuse is a significant issue among emerging adults, with harmful implications for both victims and perpetrators. This study had two main objectives: first, to validate previous findings regarding the association between victimization and perpetration of cyber dating abuse; and second, to explore the moderating role of resilience in this relationship, offering new insights into how resilience may influence these dynamics. The sample consisted of 547 participants, including 324 females and 223 males, aged 18 to 25 years ( M age = 19.95 years, SD  = 1.69). Participants completed validated scales to assess cyber dating abuse perpetration and victimization, as well as resilience, using a multi-item questionnaire. Regression analyses revealed a significant association between cyber dating abuse victimization and perpetration. Although resilience had a statistically significant moderating effect on this relationship, the strength of the moderation was weak. Preventive initiatives should take these findings into consideration when addressing cyber dating abuse. Implications for future research are also discussed.